HUBUNGAN KELENTUKAN PERGELANGAN TANGAN DENGAN ACCURACY SMASH PADA TIM BOLA VOLI PUTRA PPLP RIAU - Faradilla, Nindy Dian; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research entitled: "Wrist-Based Relationship Accuracy With Accuracy Smash on PPLP Men's Volleyball Team RIAU. This study aims to determine the correlation of wrist flexibility with accuracy smash of RRI's PPLP volleyball team. Population in this research is all volleyball team of PPLP Team of RIAU is 12 people. Sampling is done by total sampling technique. So the samples in this study are all volunteers of RIAU Team PPLP team that amounted to 20 people. This type of research is included in correlation research. Data collection was performed with wrist-formation tests and volleyball smash tests. Data obtained then processed using statistical techniques. Furthermore, the data have been obtained tested the normality with Liliefours test at a significant level α = 0.05. Based on the results of research conducted, where from the normality test data obtained Lo (X) 0.207 while Lo (Y) 0.227 and Ltabel = 0.213 so that if L0max <Ltabel then the data is normally distributed. From the calculation of product moment correlation correlation variable x to y obtained rhitung = 0.765> from rtabel thus Ho rejected and Ha diteima. Conclusion of hypothesis of this research is hypothesis accepted at significant level  = 0,05 in other words there is significant correlation between wrist flexibility with accuracy smash on RIAU PPLP volleyball team.Key Words: Wrist flexibility, smash volleyball.